An artificial delay based robust guidance strategy for an interceptor with input saturation. (March 2021) - Banerjee, Arunava; Mukherjee, Joyjit; un Nabi, Mashuq; Kar, Indra Narayan
Abstract: This paper proposes a time-energy efficient, artificial time delay based robust guidance strategy with input saturation for a two-dimensional interceptor problem. A reference near optimal heading trajectory is generated by applying Differential Evolution (DE) to the interceptor problem. By following the reference heading trajectory, the robust control law guides the missile to intercept the target in a time-energy efficient manner, while tackling the disturbances and uncertainties that it might encounter. The near optimal trajectory is obtained offline, whereas the robust guidance strategy has been applied online which further increases the appeal of the proposed guidance scheme. Uniformly ultimately bounded (UUB) stability has been affirmed for the closed loop system employing Lyapunov's method. Also, the proposed guidance law has been tested through simulation on both non-maneuvering and maneuvering targets performing bank to bank as well as step maneuver in the presence of uncertainties. Highlights: An artificial time delayed control based robust guidance law for missile-target engagement. The TDC guidance law tracks the reference time-energy efficient heading trajectory. Stability analysis ensures UUB stability of the system. Input saturation on latax is considered.